Adapting to organizational change (Center for Creative Leadership, 2013)
Annotation
Includes bibliographical references
Keywords: Organizational change; Corporate turnarounds; Organizational Innovation; Changement organisationnel; Entreprises; Redressement; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior